Front Cover: Modeling Heterogeneity in UO2 Nanoparticles Using X‐ray Absorption Spectroscopy (Eur. J. Inorg. Chem. 7/2023). Issue 7 (24th January 2023) - Bang, Shinhyo; Russo, Dominic R.; Knapp, Ashley D.; Straub, Mark D.; Smith, Kurt F.; Booth, Corwin H.; Minasian, Stefan G.; Moreau, Liane M.
Abstract : The Front Cover shows UO2 nanoparticles with a pictorial representation of the atoms (uranium in blue and oxygen in red). In this work, user‐defined X‐ray absorption spectroscopy models informed by surface relaxation effects and inherent surface disorder were generated and preferentially fit to experimentally derived data. The developed method enables representative local surface structure attributes to be extracted from bulk X‐ray absorption spectroscopy data. Results show that the UO2 surface is highly disordered compared with the bulk structure, and this cannot be explained through surface relaxation effects alone. Additionally, this trend is notably not observed in 8 nm nanoparticles (which resemble the bulk), as it is in 1.4 and 4.7 nm particles. This suggests that there may be a critical domain size for ordering within UO2 nanoparticle surfaces. More information can be found in the Research Article by L. M. Moreau and co‐workers .